(untitled) (Jurnal Sejarah Indonesia, 2025)
This article aims to explore what Sartono noticed about the field which is the "spirit" of history writing itself. The analysis process carried out in this work focuses on how the involvement of social sciences, especially in this study using a sociological approach, has had a huge influence on the methodology used by Sartono. We can understand Sartono Kartodirdjo’s historical thinking from the way he views historical events in Indonesia itself. This is inseparable from his lifetime which experienced the colonial period, independence, and post-independence revolution. From his dissertation on Banten farmers, we can see that Sartono is very sensitive to marginalized communities, and he expressed this in his excellent dissertation. He tried to challenge colonial historiography which was very Dutch in style scientifically by highlighting the role of farmers, religious figures and old aristocratic networks to be contrasted with the colonial government.